Molecular and Biochemical Analysis of Two Rice Flavonoid 3’-Hydroxylase to Evaluate Their Roles in Flavonoid Biosynthesis in Rice Grain - Sangkyu Park (International Journal of Molecular Sciences, 2016)
Anthocyanins and proanthocyanidins, the major flavonoids in black and red rice grains, respectively, are mainly derived from 3′,4′-dihydroxylated leucocyanidin. 3′-Hydroxylation of flavonoids in rice is catalyzed by flavonoid 3′-hydroxylase (F3′H: EC 1.14.13.21). We isolated cDNA clones of the two rice F3′H genes (CYP75B3 and CYP75B4) from Korean varieties of white, black, and red rice. Sequence analysis revealed allelic variants of each gene containing one or two amino acid substitutions. Heterologous expression in yeast demonstrated that CYP75B3 preferred kaempferol to other substrates, and had a low preference for dihydrokaempferol. CYP75B4 exhibited a higher preference for apigenin than for other substrates. CYP75B3 from black rice showed an approximately two-fold increase in catalytic efficiencies for naringenin and dihydrokaempferol compared to CYP75B3s from white and red rice. The F3′H activity of CYP75B3 was much higher than that of CYP75B4. Gene expression analysis showed that CYP75B3, CYP75B4, and most other flavonoid pathway genes were predominantly expressed in the developing seeds of black rice, but not in those of white and red rice, which is consistent with the pigmentation patterns of the seeds. The expression levels of CYP75B4 were relatively higher than those of CYP75B3 in the developing seeds, leaves, and roots of white rice.